2007
DOI: 10.4314/sajas.v37i2.4029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy density and L-carnitine supplementation on growth performance, carcass traits and blood parameters of broiler chickens

Abstract: The present study was conducted to determine the effects of dietary metabolisable energy (ME) density and L-carnitine supplementation on the performance, carcass traits and blood parameters of broiler chickens. The experiment was designed with three levels of dietary energy (low, medium and high) and two levels of L-carnitine (0 and 100 mg/kg diet) in a 3x2 factorial arrangement. L-carnitine supplementation did not significantly affect body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
4
29
0
5
Order By: Relevance
“…The feed efficiency was significantly better in high energy than other energy levels which coincide with the observation of Corduk et al (2007). High energy diets to broilers help maximize energy intake and this higher energy intake maximizes the growth rate (Leeson and Summers 2001).…”
Section: Discussionsupporting
confidence: 90%
“…The feed efficiency was significantly better in high energy than other energy levels which coincide with the observation of Corduk et al (2007). High energy diets to broilers help maximize energy intake and this higher energy intake maximizes the growth rate (Leeson and Summers 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Rosa et al (2007) reported that carcass chemical composition changes in different genetic groups; however, for commercial Ross 308 broilers there was reduced crude protein and increased lipid in carcass with increased dietary energy level in broilers. Others found no effect of dietary energy level on chemical composition of carcass muscle of broilers (Corduk et al 2007; Gómez-Rosales et al 2012). …”
Section: Discussionmentioning
confidence: 97%
“…It is cleared that when liver works healthy, the activity of these two enzymes in serum will reduce in broiler chickens (Corduk et al, 2007). It is reported that high fat diets could alter the related enzyme profile in serum and liver tissue (Ishii et al, 2010).…”
Section: Discussionmentioning
confidence: 99%